Women’s homelessness: causes, impact on health, survival strategies and forms of social assistance for homeless women - Mikėnė, Svajonė (Information & Media, 2018)
only abstract and keywords in English; full article, abstract and keywords in Lithuanian]This article presents a scientific literature review of foreign and Lithuanian publications revealing the specifics of women’s homelessness. The concept of homelessness, types of homelessness, general homelessness and the causes why women are becoming homeless are discussed. The peculiarities of women’s homelessness are analyzed, revealing the vulnerability of homeless women and the victimization they experience, and describes the various consequences that homelessness has for physical and mental health. The article also presents a summary of strategies applied by homeless women that help them survive on the street: they involve having an intimate partner as a protector, changing their image according to particular circumstances, strategies of invisibility and breaking the rules of public space as well as using alcohol as a means of reconciliation with homelessness. We discuss the services provided by the Special Help Centers in Lithuania, which are provided for victims of domestic violence, other specialized forms of assistance for women and social assistance measures provided by the Vilnius and Kaunas municipalities to homeless people and social risk persons. Finally, we suggest directions for future empirical research. The analysis shows that homeless women are more stigmatized and more socially excluded, and that they are more vulnerable to the effects that homelessness has on health. Violence is both a common cause of women becoming homelessness and a “companion” in during periods of homelessness. Studies conducted in foreign countries show that homeless women apply various survival strategies and tactics that increase the physical safety of women, reduce the opportunities for violence and abuse, and allow them not to feel as if they are excluded from society. The use of alcohol as a measure of reconciliation with a given situation (and often the cause of homelessness) is very widespread among homeless men and women, which, on the one hand, helps to keep in touch with other homeless people but otherwise hinders reintegration into the society. The state and its municipalities are increasingly focusing on improving social assistance and services for homeless people and social risk groups. Municipalities should carry out regular assessments of how much social assistance is focused on the individual needs of homeless women, what part of this social group it has managed to reach out to and how to measure the effectiveness/adequacy of the assistance provided.
Keywords: homeless women, domestic violence, health of the homeless, survival strategies, social assistance